Problematizing in nursing education: Freire's contribution to transformative practice. (April 2017) - Rozendo, Célia Alves; Santos Salas, Anna; Cameron, Brenda
Highlights: Problematization is a political-pedagogical act to intervene in the world. Critically questioning the world demands that we reflect and act upon events. Collective dialogue is vital to form a critical understanding of actual realities. Transformative practice must include emancipatory care to reduce inequalities.